Penerapan Green Accounting Terhadap Profitabilitas Perusahaan Di Indonesia - Tryas Chasbiandani; Nelyumna Rizal; Indra Indra Satria (AFRE (Accounting and Financial Review), 2019)
The purpose of this study is to examine the effect of green accounting and environmental performance on company profitability. Green accounting and environmental performance as an accounting benchmark for corporate awareness and concern for an increasingly old earth. This study uses a sample of 58 manufacturing companies listed on the Indonesia stock exchange in 2017 and 2018 on the basis of an assessment of PROPER. Data were analyzed using panel data analysis with the help of eviews program. The results of this study indicate that green accounting and environmental performance have a positive effect on company profitability. DOI: https://doi.org/10.26905/afr.v2i2.3722